Pengaruh Ujian Akhir Semester Terhadap Hasil Belajar Siswa Kelas XI Mata Pelajaran Geografi Di SMA Negeri 1 Gelumbang - Sakinah Sakinah; Susanti Faipri Selegi (Universitas Lambung Mangkurat, 2021)
In the world of education the term evaluation is very important because one of the competencies that must be mastered by the teacher is the evaluation of learning. One form of assessment in the learning process is a summative test that can be a determinant of the process of student learning outcomes, but in the field of evaluation and assessment there are many shortcomings in its application so researchers are interested in researching about the Evaluation of Sumative Tests on Student Learning Outcomes. This research was conducted at the State High School 1 Gelumbang using quantitative methods. Data obtained from the documentation and distribution of questionnaires to students of class XI IPS with a population of 90 people but taken as many as 60 people using random sampling techniques. The results of this study were analyzed using the hypothesis test and homogeneity test to obtain the results of this study in the form of t-count ≥ t-table (13,529> 1,995) Then it can be concluded that there is a significant influence between summative evaluation with student learning outcomes by 73%, while the remaining 27% is influenced by another factor.